Dual-Function Radar-Communications: Information Embedding Using Sidelobe Control and Waveform Diversity - Hassanien, Aboulnasr; Amin, Moeness G.; Zhang, Yimin D.; Ahmad, Fauzia (IEEE transactions on signal processing, 2016)
We develop a new technique for a dual-function system with joint radar and communication platforms. Sidelobe control of the transmit beamforming in tandem with waveform diversity enables communication links using the same pulse radar spectrum. Multiple simultaneously transmitted orthogonal waveforms are used for embedding a sequence of LB bits during each radar pulse. Two weight vectors are designed to achieve two transmit spatial power distribution patterns, which have the same main radar beam, but differ in sidelobe levels towards the intended communication receivers. The receiver interpretation of the bit is based on its radiated beam. The proposed technique allows information delivery to single or multiple communication directions outside the mainlobe of the radar. It is shown that the communication process is inherently secure against intercept from directions other than the pre-assigned communication directions. The employed waveform diversity scheme supports a multiple-input multiple-output radar operation mode. The performance of the proposed technique is investigated in terms of the bit error rate.